KI Essence extract (a spleen-tonifying formula) promotes neurite outgrowth, alleviates oxidative stress and hypomyelination, and modulates microbiome in maternal immune activation offspring - Lee, Gilbert Aaron; Zhao, Hong-Wei; Chang, Yu-Wei; Lee, Chia-Jung; Yang, Yu-Chen S. H.; Wu, Ying-Chieh; Lin, Wan-Li; Liu, Yun-Ru; Ning, De-Shan; Tseng, Sung-Hui (Frontiers in Pharmacology, 2022)
Mushrooms and Chinese traditional herbs have bioactive nutraceuticals with multiple therapeutic functions, including antioxidant and antibacterial activities and microbiome modulation properties. Mushroom-derived bioactive compounds are used in medicines for the treatment of neurological disorders with abnormal brain–gut–microbiome axis. This study examined the effects of KI Essence extract, a spleen-tonifying formula, on neurite growth, antioxidant activity, hypomyelination modulation, and the microbiome profile in lipopolysaccharide (LPS)-induced maternal immune activation (MIA) offspring. The KI Essence extract induced PC12 cell neurite growth by increasing extracellular signal–regulated kinase (ERK) phosphorylation, promoting 2,2′-diphenyl-1-picrylhydrazyl radical scavenging activity, reducing the level of tert-butylhydroperoxide–induced lipid peroxidation in brain homogenates, protecting PC12 cells from H2O2-induced cell death (through the inhibition of ERK phosphorylation), alleviating hypomyelination, and downregulating interleukin 1β through LPS-activated microglia production; moreover, the numbers of Enterobacteriaceae, Actinobacteria, Peptostreptococcaceae, Erysipelotrichaceae, and Bifidobacterium bacteria in MIA offspring increased. In summary, the KI Essence extract promotes neurite outgrowth, alleviates oxidative stress and hypomyelination, and modulates microbiota dysbiosis in MIA offspring.